An Efficacious and Secure Registration for Internet Protocol Mobility - Mathi, Senthil Kumar; Valarmathi, M.L. (Defence Science Journal, 2013)
For the ample development of mobile internet protocol (IP) technology and the recurrent movement of a mobile device, it is necessary for the mobile device to inform their home network where initially registered through an efficient and secured procedure against any sort of attacks. The procedure of registration for IP mobility by the portable system must have a better performance by providing a certain level of security, such as authentication, integrity, replay attack protection, and location privacy. All at once, the extreme security in the registration of IP mobility may cause long registration time, principally for real-time systems. This paper mainly deals with a balanced effort for secure and efficient registration procedure which gives better security and efficiency in terms of registration delay. The proposed work provides an easy and fast registration procedure and lessens the registration delay through the usage of an identity based authenticated key exchange scheme that eliminates expensive pairing operations. The proposed protocol is verified by using AVISPA tool. The performance evaluation reveals that the proposed protocol significantly outperforms the existing protocols in terms of the registration delay. Defence Science Journal, 2013, 63(5), pp.502-507, DOI:http://dx.doi.org/10.14429/dsj.63.4003